Annie0303
Rozwiązane

a) 4x - 3(3x – 5) = 6x + 4
b) 8 - (4x - 12) = 8x - (3x - 2)
c) (1 - x) – 4 = {(x – 4)+ 3 (1x
d) 7(x + 2)- x = 5(x - 2)
a) 4x – 3(x - 3) = x-4
b) 2x - (3 – 2x) = 5 + x - x
c) 5(x - 2)+(3 + x) = 6x - 7
d) -(x + 1) + 8x = 5x - 9 ​



Odpowiedź :

Odpowiedź:

Szczegółowe wyjaśnienie:

a)4x-3(3x-5)=6x+4

4x-9x+15=6x+4

-5x+15=6x+4

x=19

b) 8-(4x-12)=8x-(3x-2)

8-4x+12=8x-3x+2

-4x-8x+3x=2-12

-9x=-10 /÷ (-9)

x=10/9

c) coś Ci się zgubiło, nie mogę pomóc :/

d) 7(x+2)-x=5(x-2)

7x+14-x=5x-10

7x-x-5x=-10-14

-13x=-24 /÷(-13)

x=1 11/13

a)4x-3(x-3)=x-4

 4x-3x+9=x-4

 x+9=x-4

 x-x=-4-9

 0=13

b)2x-(3-2x)=5+x-x

  2x-3+2x=5+0

  2x+2x=5+3

  4x=8 /÷4

  x=2

c)5(x-2)+(3+x)=6x-7

  5x-10+3+x=6x-7

  5x-7+x=6x-7

   5x-x=6x   (Mogę skrócić i dlatego nie ma tych -7)

    -2x=0 /÷(-2)

      x=0

  d)-(x+1)+8x=5x-9

    -x-1+8x=5x-8

     -x+8x-5x=-8+1

      2x=-7 /÷2

      x=-7/2